Respon Harga Saham Transportasi Darat Terhadap Kenaikan Bahan Bakar Minyak Bersubsidi 2022 - Hendro Lukman (Universitas Kristen Maranatha, 2023)
The policy of increasing the price of Subsidized Fuel Oil (subsidized fuel) will have animpact on the community, both directly and indirectly. For the society, the increase insubsidized fuel directly increases transportation expenditures, and indirectly throughincreases in goods and services. For companies, especially inland transportationcompanies, it has an impact on operating expenses and can reduce revenue. This research isan event study to see the effect of inland transportation companies’ share listed on theIndonesia Stock Exchange due to the announcement of the increase in subsidized fuel. Theresults of this event study showed that 1 day and 5 days before the announcement showed nodifference with 1 day and 5 days after the announcement of the increase in subsidized fuel.This study explains that inland transportation companies have anticipated that the stockmarket will not cause negative movements, it is because the government provides anexplanation a few days before the announcement date. The implications of this study showthat providing reliable explanations and information to society can reduce turmoil in thecapital market, and businessmen can anticipate the policies that will be announced.Keywords: Inland Transportation, Subsidized Fuel, Event Study, Economic Announcement